2003
DOI: 10.1016/s1090-5138(02)00105-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of kin on female fertility in rural Gambia

Abstract: This is an electronic version of an Article published in Evolution and AbstractHuman females reproduce relatively rapidly throughout their reproductive years compared to the other great apes. It has been suggested that women are able to sustain this rapid pace by co-opting family members to help raise their children. We tested the hypothesis that the presence of kin will increase the reproductive rates of women using a longitudinal database collected from rural Gambia. We found that both the husband's mother a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
127
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 42 publications
4
127
1
Order By: Relevance
“…If women have generally incurred greater fitness costs of reproduction, this life history tradeoff could help explain why they generally prefer fewer offspring than their husbands and reduce their fertility when they obtain more reproductive autonomy (23). Conflicts over family size often involve in-laws, and our findings help to explain why the presence of maternal in-laws lower a couple's fertility, whereas paternal in-laws increase it (55,56): maternal in-laws have more evolutionary interests in the mother's health and reproductive costs than paternal kin. Thus, sexual asymmetries in reproductive costs and investment may contribute to familial and sexual conflicts (20).…”
Section: Discussionmentioning
confidence: 69%
“…If women have generally incurred greater fitness costs of reproduction, this life history tradeoff could help explain why they generally prefer fewer offspring than their husbands and reduce their fertility when they obtain more reproductive autonomy (23). Conflicts over family size often involve in-laws, and our findings help to explain why the presence of maternal in-laws lower a couple's fertility, whereas paternal in-laws increase it (55,56): maternal in-laws have more evolutionary interests in the mother's health and reproductive costs than paternal kin. Thus, sexual asymmetries in reproductive costs and investment may contribute to familial and sexual conflicts (20).…”
Section: Discussionmentioning
confidence: 69%
“…Some evidence indicates that sons, as the more expensive sex to rear, reduce investment in all later born offspring measured by reductions in birth weight (Nielsen et al 2008), adult height (Rickard 2008) and reproductive success (Rickard, Russell, andLummaa 2007, Sear, Mace, andMcGregor 2003). Sons may receive more investment from parents because they can benefit more, in terms of reproductive success, from parental resources than daughters can.…”
Section: Introductionmentioning
confidence: 99%
“…Alloparents are individuals other than the biological parents who invest in children. They have been shown to increase maternal reproductive success (Bereczkei and Dunbar 2002;Sear et al 2003) and aid in infant survivorship (Hawkes et al 1997;Ivey 2000). Studies have shown that humans are cooperative childrearers and that successful rearing of offspring may be dependent on alloparental assistance (Hrdy 2005;Ivey 2000).…”
mentioning
confidence: 99%
“…Alloparents in many species behave in a way that results in these maternal benefits, but Hrdy (2005) notes that lengthy human lifespans have made it difficult for many researchers to examine the overall impact that alloparents have on maternal reproductive success. However, several studies among humans illustrate that alloparents can lower maternal costs and increase maternal reproductive success (Flinn 1989;Kramer 2002;Sear et al 2003;Turke 1988).…”
mentioning
confidence: 99%